A global analysis of extreme coastal water levels with implications for potential coastal overtopping - Rafael Almar (Nature Portfolio, 2021)
As sea levels rise, coasts are being increasingly  threatened by overtopping caused by the combination of sea level rise, storm surge and wave runup. Here the authors find that global coastal overtopping has increased by over 50% in the last two decades, and under a RCP 8.5 scenario this could increase up to 50 times by 2100 compared to today.